2021
DOI: 10.2166/ws.2021.142
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of ecosystem evapotranspiration in aRobinia pseudoacaciaL. plantation with the use of the eddy covariance technique and modeling approaches

Abstract: Τhe eddy covariance technique provides reliable ecosystem-level ET measurements. These measurements, when combined with models and satellite products, could offer high spatiotemporal coverage and valuable mechanistic interpretation of the underlying processes. This study address one-year eddy covariance measurements from a Robinia pseudoacacia site in Northern Greece and remote sensing products, we (a) provide a medium-term description of daily ET fluxes for a R. pseudoacacia plantation in a degraded land, (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…8). Markos and Radoglou (2021) reported that evapotranspiration was mostly affected by soil moisture and net radiation.…”
Section: Soil Water Contentmentioning
confidence: 99%
“…8). Markos and Radoglou (2021) reported that evapotranspiration was mostly affected by soil moisture and net radiation.…”
Section: Soil Water Contentmentioning
confidence: 99%
“…This SI presents characteristic examples of new technologies and decision support systems (e.g., artificial intelligence/ optimization modelling approaches, Big Geo data) in water efficiency at different levels, including: water supply hydraulic infrastructure systems, water retention measures, less exposed to evaporation and better adapted to infiltration, solutions to reduce water demand and developing techniques for reusing water. Specifically, this SI brings advances in precision irrigation techniques adapted to the actual needs of plants at farm and extended scale applications (Filintas et al 2021;Markos & Radoglou 2021;Mousabeygi et al 2021). Also, new modelling approaches to predict and/or monitor water dynamics (Kader et al 2021;Mridha & Rahman 2021;Sihag et al 2021;Tziatzios et al 2021;Xu et al 2021) or pollutants transport such as salinity (Daghari et al 2021;Yuan 2021) and nitrates (Bian et al 2021;Nie et al 2021) are provided.…”
Section: This Special Issuementioning
confidence: 99%
“…Meteorological and soil water conditions may strongly affect ecosystem water and carbon fluxes through their control of canopy transpiration and evapotranspiration [7][8][9], as well as ecosystem productivity [10], which is driven by plant photosynthesis. At a Forests 2023, 14, 916 2 of 15 short temporal scale, the optimum equilibrium between maximizing photosynthesis and minimizing water losses through transpiration is governed by stomatal responses to solar radiation and vapor pressure deficit-VPD [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] and the literature therein). However, to our knowledge, there is scarce information on the ecophysiological responses of black locust forests or plantations to climatic drivers at the ecosystem level [8], particularly when it comes to data collected by eddy flux towers [9]. The accurate determination of black locust GPP and ET by means of Eddy Covariance will provide the necessary ground measurements for the development, calibration and cross-validation of ecological, biogeochemical and satellite-based models for the prediction of these parameters (e.g., [34][35][36][37][38]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation